Risk factors for non-communicable diseases in Bangladesh: findings of the population-based cross-sectional national survey 2018 - Baizid Khoorshid Riaz; Md Ziaul Islam; A N M Shamsul Islam; M M Zaman; Md Akram Hossain; Md Mujibur Rahman; Fahmida Khanam; K M Bayzid Amin; Irfan Nowroze Noor (BMJ Open)
Objectives To determine the national prevalence of risk factors of non-communicable diseases (NCD) in the adult population of Bangladesh.Design The study was a population-based national cross-sectional study.Setting This study used 496 primary sampling units (PSUs) developed by the Bangladesh Bureau of Statistics. The PSUs were equally allocated to each division and urban and rural stratum within each division.Participants The participants were adults aged 18 to 69 years, who were usual residents of the households for at least 6 months and stayed the night before the survey. Out of 9900 participants, 8185 (82.7%) completed STEP-1 and STEP-2, and 7208 took part in STEP-3.Primary and secondary outcome The prevalence of behavioural, physical and biochemical risk factors of NCD. Data were weighted to generate national estimates.Results Tobacco use was significantly (p<0.05) higher in the rural (45.2%) than the urban (38.8%) population. Inadequate fruit/vegetable intake was significantly (p<0.05) higher in the urban (92.1%) than in the rural (88.9%) population. The mean salt intake per day was higher in the rural (9.0 g) than urban (8.9 g) population. Among all, 3.0% had no, 70.9% had 1 to 2 and 26.2% had ≥3 NCD risk factors. The urban population was more likely to have insufficient physical activity (adjusted OR (AOR): 1.2, 95% CI: 1.2 to 1.2), obesity (AOR: 1.5, 95% CI: 1.5 to 1.5), hypertension (AOR: 1.3, 95% CI: 1.3 to 1.3), diabetes (AOR: 1.6, 95% CI: 1.6 to 1.6) and hyperglycaemia (AOR: 1.1, 95% CI: 1.1 to 1.1).Conclusions Considering the high prevalence of the behavioural, physical and biochemical risk factors, diverse population and high-risk group targeted interventions are essential to combat the rising burden of NCDs.